The FLP proteins act as regulators of chlorophyll synthesis in response to light and plastid signals in Chlamydomonas - Falciatore, Angela (Cold Spring Harbor Laboratory Press, 2005)
In photosynthetic organisms the accumulation of harmful photodynamic chlorophyll precursors is prevented because of the tight regulation of the tetrapyrrole pathway. FLU is one of the regulatory factors involved in this process in land plants. We have examined the function of a Flu-like gene (FLP) from Chlamydomonas that gives rise to two FLP transcripts through alternative splicing. These transcripts are translated into a short and a long protein that differ by only 12 amino acids but that interact differently with glutamyl-tRNA reductase, an enzyme involved in an early step of the chlorophyll biosynthetic pathway. Expression of FLPs is light-regulated at the level of RNA accumulation and splicing and is altered by mutations affecting the pathway. The relative levels of the long and short forms of FLP can be correlated with the accumulation of specific porphyrin intermediates, some of which have been implicated in a signaling chain from the chloroplast to the nucleus. Reciprocally, reduction of the FLP proteins by RNA interference leads to the accumulation of several porphyrin intermediates and to photobleaching when cells are transferred from the dark to the light. Thus the FLP proteins act as regulators of chlorophyll synthesis, and their expression is controlled by light and plastid signals.